Scaling climate-smart innovations in Zambia - Jacobs Mata, Inga; Amarnath, Giriraj; Kakwasha, Keagan; Pele, Winnie; Makungwe, Mirriam; Dhulipala, Ram; Dirwai, Tinashe Lindel; Mudege, Netsayi N; Ewell, Hanna Louise Deborah; Carbonell Barlis, Angelica; Zougmore, Robert Bellarmin (2025)
AICCRA Zambia has moved from piloting to systemic scaling of bundled CSA and CIS through an inclusive lens. Through accelerator partnerships with agribusinesses, digital platforms like the AgDataHub, media campaigns, and multi-stakeholder platforms, Zambia’s model bundles advisories, inputs, and finance while aligning with national policies and mobilizing private sector engagement. Between 2021 and 2025, these efforts reached more than 2.5 million people, demonstrating that strategic partnerships, inclusive business and delivery models, and adaptive scaling approaches can transform how innovations spread.